Beyond modularity : a developmental perspective on cognitive science - Karmiloff-Smith, Annette (MIT Press, 1996)
Taking a stand midway between Piaget's constructivism and Fodor's nativism, Annette Karmiloff-Smith offers an exciting new theory of developmental change that embraces both approaches. She shows how each can enrich the other and how both are necessary to a fundamental theory of human cognition. Karmiloff-Smith shifts the focus from what cognitive science can offer the study of development to what a developmental perspective can offer cognitive science. In Beyond Modularity she treats cognitive development as a serious theoretical tool, presenting a coherent portrait of the flexibility and creativity of the human mind as it develops from infancy to middle childhood. Language, physics, mathematics, commonsense psychology, drawing, and writing are explored in terms of the relationship between the innate capacities of the human mind and subsequent representational change which allows for such flexibility and creativity. Karmiloff-Smith also takes up the issue of the extent to which development involves domain-specific versus domain-general processes. She concludes with discussions of nativism and domain specificity in relation to Piagetian theory and connectionism, and shows how a developmental perspective can pinpoint what is missing from connectionist models of the mind.
"A Bradford book."
Keywords: Cognition in children.; Modularity (Psychology) in children.; Constructivism (Psychology); Nativism (Psychology); Child development.; Child psychology.; Cognition.; Infants.; Children.; Child Development; Psychology, Child; Cognition; Child Behavior; Infant; Child; Cognition chez l'enfant.; Modularité chez l'enfant.; Constructivisme (Psychologie); Nativisme (Psychologie); Enfants -- Développement.; Enfants -- Psychologie.; Nourrissons.; Enfants.; Enfance.; cognition.; infants.; children (people by age group); childhood.; PSYCHOLOGY -- Developmental -- Child.; PSYCHOLOGY -- Psychotherapy -- Child & Adolescent.; FAMILY & RELATIONSHIPS -- Child Development.; Infants; Children; Child psychology; Child development; Cognition in children; Modularity (Psychology) in children; Kognitive Psychologie; Kognitive Entwicklung; Entwicklungspsychologie; COGNITIVE SCIENCES/General; COGNITIVE SCIENCES/Psychology/Cognitive Psychology; Online resources.